Study of Y(3S,2S) → [eta]Y(1S) and Y(3S,2S) → π+π-Y(1S) hadronic transitions - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study the Υ(3S,2S)→ηΥ(1S) and Υ(3S,2S)→π+π−Υ(1S) transitions with 122×106Υ(3S) and 100×106Υ(2S) mesons collected by the BABAR detector at the PEP-II asymmetric-energy e+e− collider. We measure B[Υ(2S)→ηΥ(1S)]=(2.39±0.31(stat.)±0.14(syst.))×10−4 and Γ[Υ(2S)→ηΥ(1S)]/Γ[Υ(2S)→π+π−Υ(1S)]=(1.35±0.17(stat.)±0.08(syst.))×10−3. We find no evidence for Υ(3S)→ηΥ(1S) and obtain B[Υ(3S)→ηΥ(1S)]<1.0×10−4 and Γ[Υ(3S)→ηΥ(1S)]/Γ[Υ(3S)→π+π−Υ(1S)]<2.3×10−3 as upper limits at the 90% confidence level. We also provide improved measurements of the Υ(2S)−Υ(1S) and Υ(3S)−Υ(1S) mass differences, 562.170±0.007(stat.)±0.088(syst.) MeV/c2 and 893.813±0.015(stat.)±0.107(syst.) MeV/c2, respectively.
Im Titel ist [eta] als griechischer Buchstabe dargestellt
Im Titel sind das Plus- und Minuszeichen hochgestellt
Gesehen am 15.08.2022